First confirmed record of the Tigris cat, Glyptothorax cous (Linnaeus, 1766) in southern Iraq - Al-Faisal, Abbas (Iraqi Journal of Aquaculture, 2025)
The Tigris cat, Glyptothorax cous (Linnaeus, 1766) (seven specimens) was collected from lower part of the Tigris River in Al-Qurna district, southern Iraq. The current report represents the new record for Tigris cat in the south of Iraq. G. cous is characterized by having a flat head, small adipose fin, head, back and flank usually have large, bony, striated and elongated tubercles.